Modified laser-assisted lip repositioning surgery to treat gummy smile - Sana Farista; Aditi Chaudhary; Balaji Manohar; Shanin Farista; Rufi Bhayani (Wolters Kluwer Medknow Publications, 2021)
Excessive gingival display (EGD), known as "gummy smile," is a major esthetic hurdle in today's population. The condition occurs due to various etiologies such as skeletal, dentoalveolar, or soft-tissue origin. The treatment modalities range from orthognathic surgery to periodontal plastic procedures. Lip-repositioning surgery (LRS) is a better alternative for the conventional orthognathic surgery and laser-assisted LRS can be a reliable and a less invasive alternative to conventional (scalpel) LRS. The present case describes the successful treatment of a young female exhibiting an EGD caused by hypermobility of the upper lip and was treated with a modified laser-assisted LRS coupled with gingival recontouring. In a study published earlier, a mild recurrence was observed and hence, to overcome the recurrence, a modified technique, by excising a strip of mucosa with an additional 2 mm of tissue along with the muscular attachment rather than scraping, was attempted.